(untitled) (قضايا سياسية, 2023)
Despite the adoption of many legislations and laws that punish people, entities, institutions and employers when they employ children in dangerous professions and for long hours that are not consistent with the physical and psychological capabilities of most children, which represents a serious threat to the future of childhood, especially in Iraq after 2003. After the year (2003), Iraq was subjected to conditions of political and security instability, which were reflected in the Iraqi societal reality, especially the economic and social reality. Kabir, and hundreds of thousands of orphans and widows, and families headed by women, which forced many of these vulnerable groups to push their children into the labor market early, due to the lack of human security for many of them, which made many children move away from school seats, and live in living and psychological conditions Difficult The expansion of the phenomenon of child labor in Iraq has many societal effects, whether political, security, economic and social, that could threaten the societal reality in Iraq, given that children are the backbone of development, and they are the men of tomorrow, and the pillar of the future, which requires the Iraqi political decision-maker to develop remedies and solutions for those Dangerous phenomenon, and according to a targeted government program, and rational public policies in legislation and implementation